Ginkgolide C Alleviates Myocardial Ischemia/Reperfusion-Induced Inflammatory Injury via Inhibition of CD40-NF-κB Pathway - Zhang, Rui; Han, Dan; Li, Zhenyu; Shen, Chengwu; Zhang, Yahui; Li, Jun; Yan, Genquan; Li, Shasha; Hu, Bo; Li, Jiangbing; Liu, Ping (Frontiers in Pharmacology, 2018)
Increasing evidence shows that inflammation plays a vital role in the occurrence and development of ischemia/reperfusion (I/R). Suppression of excessive inflammation can ameliorate impaired cardiac function, which shows therapeutic potential for clinical treatment of myocardial ischemia/reperfusion (MI/R) diseases. In this study, we investigated whether Ginkgolide C (GC), a potent anti-inflammatory flavone, extenuated MI/R injury through inhibition of inflammation. In vivo, rats with the occlusion of the left anterior descending (LAD) coronary artery were applied to mimic MI/R injury. In vitro, primary cultured neonatal ventricular myocytes exposed to hypoxia/reoxygenation (H/R) were applied to further discuss the anti-H/R injury property of GC. The results revealed that GC significantly improved the symptoms of MI/R injury, as evidenced by reducing infarct size, preventing myofibrillar degeneration and reversing the mitochondria dysfunction. Moreover, histological analysis and Myeloperoxidase (MPO) activity measurement showed that GC remarkably suppressed Polymorphonuclears (PMNs) inﬁltration and ameliorated the histopathological damage. Furthermore, GC pretreatment was shown to improve H/R-induced ventricular myocytes viability and enhance tolerance of inflammatory insult, as evidenced by suppressing expression of CD40, translocation of NF-κB p65 subunit, phosphorylation of IκB-α, as well as the activity of IKK-β. In addition, downstream inflammatory cytokines modulated by NF-κB signaling were effectively down-regulated both in vivo and in vitro, as determined by immunohistochemistry and ELISA. In conclusion, these results indicate that GC possesses a beneficial effect against MI/R injury via inflammation inhibition that may involve suppression of CD40-NF-κB signal pathway and downstream inflammatory cytokines expression, which may offer an alternative medication for MI/R diseases.